2020
DOI: 10.48550/arxiv.2003.04644
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Periodic Fast Radio Bursts as a Probe of Extragalactic Asteroid Belts

Z. G. Dai,
S. Q. Zhong

Abstract: The periodic activity of repeating fast radio burst (FRB) 180916.J0158+65 was recently reported by the CHIME/FRB Collaboration team. 28 bursts from this source not only show a ∼ 16-day period with an active phase of ∼ 4.0 days but also indicate a broken power law in differential energy distribution. In this paper, we suggest that FRB 180916.J0158+65-like periodic FRBs would provide a unique probe of extragalactic asteroid belts (EABs), based on our previously-proposed pulsar-EAB impact model, in which repeatin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…The ∼ 16-day periodicity of FRB 180916.J0158+65 Marcote et al (2020b) may require a binary systems (e.g. Ioka & Zhang 2020;Lyutikov et al 2020;Katz 2020;Dai & Zhong 2020). These systems may have a host galaxy or local environment similar to intermediate stellar populations.…”
Section: Resultsmentioning
confidence: 99%
“…The ∼ 16-day periodicity of FRB 180916.J0158+65 Marcote et al (2020b) may require a binary systems (e.g. Ioka & Zhang 2020;Lyutikov et al 2020;Katz 2020;Dai & Zhong 2020). These systems may have a host galaxy or local environment similar to intermediate stellar populations.…”
Section: Resultsmentioning
confidence: 99%
“…The reported periodicity is far too long to be ascribed to a neutron star's rotational frequency, and triggered a wealth of alternative hypotheses, such as orbital effects (Lyutikov et al 2020;Ioka & Zhang 2020) or various kinds of precessional effects (Yang & Zou 2020;Levin et al 2020;Zanazzi & Lai 2020;Gu et al 2020) or other secular semi-periodic cyclic phenomena, e.g. the source traveling across an asteroid belt (Dai & Zhong 2020). Most of these models revisited concepts developed for the modeling of the original RFRB (for a review see Platts et al 2019), tuned to a ∼ 16 days periodicity.…”
Section: Introductionmentioning
confidence: 99%
“…NS and massive star binary to interpret the periodicity of FRB 180916, but they proposed that the observed periodicity is due to the orbital phase-dependent modulation of the absorption conditions in the massive star's wind, instead of intrinsic to the FRBs' source. Dai & Zhong (2020) propose that periodically repeating FRB might be produced from an old-aged pulsar traveling through the asteroid belts of its companion star, so that the periodically repeating FRBs would provide a unique probe of extragalactic asteroid belts. Gu et al (2020) suggested that FRB 180916 is produced by a NS-white dwarf (WD) binary system when the WD fills its Roche lobe at the pericenter, so that the mass transfer from the WD to the NS resulting in multiple radio bursts.…”
Section: Introductionmentioning
confidence: 99%